REACTIVITY OF ANTI-CAPSID MONOCLONAL ANTIBODIES WITH NATIVE AD RECOMBINANT PROTEIN OF JEMBRANA DISEASE VIRUS REAKTIVITAS ANTIBODI MONOKLONAL ANTI-KAPSID DENGAN PROTEIN NATIF DAN PROTEIN REKOMBINAN VIRUS PENYAKIT JEMBRANA - Mantik Astawa, Nyoman (Jurnal Veteriner; Vol 8 No 2 (2007))
Reactivity of anti-capsid monoclonal antibody (mAbs) with both native and recombinant protein of Jembrana Disease Virus (JDV) was examined. The monocloncal antibodies were produced by fusion of my.loma cells with lymphocytes of mice immunized with JDV antigen. Ten mAbs were produced and they designated as CC12, BB7, AH7, BD2, DB2, AF9, BC10, AG7, AH4 and CB11. In ELISA test, all mAbs reacted with recombinant proteins (glutation-8-transferase-capsid/GST-Ca and histidine tagged capsid/His-Ca) but not with GST alone.
Keywords: antibody, monoclonal, capsid, Jembrana, disease, virus